Plug-and-play design and distributed logic control of medical devices using IEC 61499 function blocks. (1st January 2013) - Sorouri, Majid; Vyatkin, Valeriy; Xie, Shengquan; Salcic, Zoran
Plug-and-play control design and interoperability of medical devices has now become a decisive mission of technological research. One of the reasons for these requirements is the ever increasing attention that the medical sector is paying these days to specific treatments each individual patient requires which mandates having medical devices that are customisable and, more importantly, are able to interact with each other to handle more complex tasks and, as well, avoid more risks. Currently, vendor-specific devices and proprietary communication systems have hindered clinical environments from thoroughly reaching these goals. Thus, this paper concentrates on the software development aspect of medical devices and proposes a novel approach for the development of distributed control logic for them using modular, reusable and interoperable software components based on the IEC 61499 function blocks (FB). This technology enables the control design of the entire application to be in one software tool and consequently, alleviates design complexity and development time. Following that, it presents a simplified case study to exhibit the viability of this methodology to be exploited for control software design of medical and rehabilitation devices.